Penyuluhan Hukum Oleh Notaris Mengenai Status Hukum BUMDES Pasca Pemberlakuan Peraturan Pemerintah Nomor 11 Tahun 2021 tentang Badan Usaha Milik Desa - Urip Tri Riski Setyaningrum (Faculty of Law Universitas Islam Indonesia, 2022)
Article 117 of Law Number 11 of 2020 on Job Creation changes Village-Owned Enterprises from previously business entities to legal entities. The future consequence is that Village Owned Enterprises are included in one of the legal subjects. Previously, it was sufficient to ratify the Village Regulations without having a notarial deed. In fact, the function of an authentic deed made by a Notary is related to the perfect strength of proof. The existence of the authority of a Notary to be able to conduct legal counseling in connection with the making of a deed as stipulated in Article 15 paragraph (2) letter e of Law Number 2 of 2014 on the Notar Public.Thus, the researcher formulates the following formulation of the problem: what is the role of the notary in legal counseling regarding the legal status of Village-Owned Enterprises after the enactment of Government Regulation Number 11 of 2021 on Village-Owned Enterprises? The research method used is normative with library research. The results of the study concluded that notaries in legal counseling can basically be limited to making deed of establishment of Village Owned Enterprises as legal entities, not requiring direct visits to each village to then influence residents to use their services. This is clearly prohibited in the Notary Code of Ethics, because a Notary is not a consultant on all legal issues.Key Word: Legal Counseling, Notary, BUMDES AbstrakPasal 117 Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja merubah Badan Usaha Milik Desa dari semula badan usaha menjadi badan hukum. Konsekuensi kedepannya, Badan Usaha Milik Desa termasuk dalam salah satu subyek hukum. Sebelumnya, pengesahan Peratuan Desa cukup dibuat tanpa adanya akta notaris. Padahal, fungsi akta autentik yang dibuat notaris ada berkaitan dengan kekuatan pembuktian yang sempurna. Adanya kewenangan notaris untuk dapat melakukan penyuluhan hukum sehubungan dengan pembuatan akta sebagaimana diatur dalam Pasal 15 ayat (2) huruf e Undang-Undang Nomor 2 Tahun 2014 tentang Jabatan Notaris. Sehingga, peneliti merumuskan rumusan masalah bagaimanakah peran notaris dalam penyuluhan hukum mengenai status hukum Badan Usaha Milik Desa pasca pemberlakuan Peraturan Pemerintah Nomor 11 Tahun 2021 tentang Badan Usaha Milik Desa. Metode penelitian yang digunakan adalah normatif dengan studi kepustakaan. Hasil penelitian menyimpulkan bahwa notaris dalam penyuluhan hukum pada dasarnya dapat dilakukan terbatas pada pembuatan akta pendirian Badan Usaha Milik Desa sebagai badan hukum, tidak memerlukan kunjungan langsung ke setiap desa untuk kemudian mempengaruhi warga untuk menggunakan jasanya. Hal ini jelas dilarang dalam Kode Etik Notaris, karena Notaris bukanlah seorang konsultan mengenai semua persoalan hukum.Kata-kata Kunci: Penyuluhan Hukum, Notaris, BUMDES.